The positioning of stress fibers in contractile cells minimizes internal mechanical stress - Riedel, Lukas; Wössner, Valentin; Kempf, Dominic; Ziebert, Falko; Bastian, Peter; Schwarz, Ulrich S. (Journal of the mechanics and physics of solids, 2025)
The mechanics of animal cells is strongly determined by stress fibers, which are contractile filament bundles that form dynamically in response to extracellular cues. Stress fibers allow the cell to adapt its mechanics to environmental conditions and to protect it from structural damage. While the physical description of single stress fibers is well-developed, much less is known about their spatial distribution on the level of whole cells. Here, we combine a finite element method for one-dimensional fibers embedded in an elastic bulk medium with dynamical rules for stress fiber formation based on genetic algorithms. We postulate that their main goal is to achieve minimal mechanical stress in the bulk material with as few fibers as possible. The fiber positions and configurations resulting from this optimization task alone are in good agreement with those found in experiments where cells in 3D-scaffolds were mechanically strained at one attachment point. For optimized configurations, we find that stress fibers typically run through the cell in a diagonal fashion, similar to reinforcement strategies used for composite material.
Online verfügbar 18 November 2024, Version des Artikels 23 November 2024
Gesehen am 02.06.2025